What Brexit means for EU and UK social policy - Hantrais, Linda (Policy Press shorts. Policy & practice., 2019)
With the UK's decision to leave the EU as one of the greatest challenges in the EU's history, this book seeks to understand the role played by social policy in the referendum campaign and withdrawal negotiations, and considers what Brexit means for social policy development both in the UK and across the EU.